Cauchy problem for matrix factorizations of the Helmholtz equation - Zhuraev, D. A. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study the Cauchy problem for a system of elliptic equations of the first order with constant coefficients factorizing theHelmholtz operator in a two-dimensional bounded domain. An approximate solution of this problem based on the methodof Carleman matrix is constructed.